Chlamydia psittaci, chlamydia avium and psittacidae herpesvirus in the burrowing parrot (cyanoliseus patagonus) colony of argentine patagonia - Origlia, Javier (2022)
Fil: Origlia, Javier. Universidad Nacional de La Plata, Facultad de Ciencias Veterinarias, Catedra de Patología de Aves y Pilíferos. La Plata, Buenos Aires Argentina